2008
DOI: 10.1111/j.1469-8749.2008.02029.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of motor impairment in children with cerebral palsy

Abstract: Classification of the quality and topographical pattern of motor impairment is used to describe cerebral palsy (CP). As an adjunct to a study characterizing the quality of life and participation of school-age children with CP, initial and follow-up classification of CP were compared. A cohort of 93 children (58 males, 35 females) were initially assessed at a mean age of 2 years 6 months (SD 2y 2mo) and re-assessed at 9 years 4 months (SD 2y 2mo) with a mean interval of 6 years 6 months (SD 2y 4mo) between asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…The figures presented in this table clearly demonstrate that preterm birth is the most important determinant of CP with an overall prevalence of 1% versus 0.07% in infants born at term. This finding, which also corresponds with a large Norwegian study, 4 is not commented upon. The majority of infants with CP with breech presentation was found in the preterm group and the CP cases were equally distributed between term (n=112) and preterm (n=107) deliveries, contrary to a large…”
Section: Michael Shevellsupporting
confidence: 82%
See 1 more Smart Citation
“…The figures presented in this table clearly demonstrate that preterm birth is the most important determinant of CP with an overall prevalence of 1% versus 0.07% in infants born at term. This finding, which also corresponds with a large Norwegian study, 4 is not commented upon. The majority of infants with CP with breech presentation was found in the preterm group and the CP cases were equally distributed between term (n=112) and preterm (n=107) deliveries, contrary to a large…”
Section: Michael Shevellsupporting
confidence: 82%
“…Indeed, we have reported that neurological subtype may vary over time in a subset (approximately 25%). 4 This variation tends to occur in particular subtypes (i.e. quadriplegic and dyskinetic) and is likely to reflect the influence of central nervous system maturational and contextual factors.…”
Section: Michael Shevellmentioning
confidence: 99%
“…Independent neurologic examination confirmed the persisting diagnosis of CP, as per Badawi et al [16,17]. Children included in this study on inter-rater reliability were those in whom the parent and the research coordinator agreed that the child had the cognitive and language ability to self-report (either independently or with the assistance of the coordinator, by interview) to complete the PedsQL (child version).…”
Section: Subjectsmentioning
confidence: 90%
“…Cerebral Palsy (CP) refers to a group of permanent disorders in the development of motor and postural control that are of cerebral origin, acquired either before birth or during the first years of life (Rosenbaum et al, 2007;Shevell, Majnemer, Poulin, & Law, 2008). It is the leading cause of motor impairments in childhood (Kerr, McDowell, Parkes, Stevenson, & Cosgrove, 2011) with an estimated incidence of 2-3 occurrences per every 1000 live births in the developed world (Andersen, 2011).…”
Section: Introductionmentioning
confidence: 99%